2012
DOI: 10.3133/ds718
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater-quality and quality-control data for two monitoring wells near Pavillion, Wyoming, April and May 2012

Abstract: Appendix 1. Monitoring Well MW01 field notes-Field instrument calibration notes, general project notes, groundwater-quality notes for samples 1 and 2, alkalinity/acid neutralizing capacity titration field notes and results (figures 1.1.1-1.3.2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 1 publication
0
19
0
2
Order By: Relevance
“…The culprit is believed to be an improperly cemented well [ Mordick , ]. In 2008, home owners living near Pavillion, WY complained to the U.S. EPA about the taste and odor of their well water [ DiGiulio et al ., ]. The EPA's initial study found many chemicals associated with HF fluids in the aquifer and claimed that they were likely due to HF [ DiGiulio et al ., ], but questions about the methodology arose [ Wright et al ., ; Vidic et al ., ]. The U.S. EPA, the U.S. Geological Survey, and the Wyoming Department of Environmental Quality have all studied this site, and the investigation is ongoing [ DiGiulio et al ., ; Wright et al ., ].The geology and drilling depths make the Pavillion, WY case somewhat unique from many shale gas plays.…”
Section: Discussion Suggestions For Future Modeling and Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…The culprit is believed to be an improperly cemented well [ Mordick , ]. In 2008, home owners living near Pavillion, WY complained to the U.S. EPA about the taste and odor of their well water [ DiGiulio et al ., ]. The EPA's initial study found many chemicals associated with HF fluids in the aquifer and claimed that they were likely due to HF [ DiGiulio et al ., ], but questions about the methodology arose [ Wright et al ., ; Vidic et al ., ]. The U.S. EPA, the U.S. Geological Survey, and the Wyoming Department of Environmental Quality have all studied this site, and the investigation is ongoing [ DiGiulio et al ., ; Wright et al ., ].The geology and drilling depths make the Pavillion, WY case somewhat unique from many shale gas plays.…”
Section: Discussion Suggestions For Future Modeling and Conclusionmentioning
confidence: 99%
“…The EPA's initial study found many chemicals associated with HF fluids in the aquifer and claimed that they were likely due to HF [ DiGiulio et al ., ], but questions about the methodology arose [ Wright et al ., ; Vidic et al ., ]. The U.S. EPA, the U.S. Geological Survey, and the Wyoming Department of Environmental Quality have all studied this site, and the investigation is ongoing [ DiGiulio et al ., ; Wright et al ., ].The geology and drilling depths make the Pavillion, WY case somewhat unique from many shale gas plays. First of all, the target formation, the Lower Wind River formation, is a sandstone rather than a shale [ Wright et al ., ], and would therefore have a higher permeability associated with it.…”
Section: Discussion Suggestions For Future Modeling and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Case studies of isolated groundwater contamination incidents suggest links with shale gas activity. For example, in Pavilion, Wyoming, studies by two federal agencies found contamination in groundwater wells from shale gas activities [52,53]. In Alberta, an energy developer inadvertently fractured a shale gas well above its intended subsurface target, contaminating groundwater in the process [54].…”
Section: Groundwater Quality Impactsmentioning
confidence: 99%
“…The Pavillion gas field is in the western portion of the Wind River Basin in Fremont County near the town of Pavillion, population 231, in west central Wyoming within the Wind River Indian Reservation (Wright et al ) (Figure S1, Supporting information). The basin is flanked by the Wind River Range, the Absaroka Range, and the Owl Creek Mountains.…”
Section: Site Description and Groundwater Conditionsmentioning
confidence: 99%